Crossmodal associations between flavoured milk solutions and musical notes. - Crisinel, A; Spence, C (2011)
A number of crossmodal associations have now been described in the context of food evaluation, such as between tastes or flavours and musical notes (Crisinel and Spence, 2010b). Here we extend these findings by presenting flavoured milk solutions of varying fat contents. The participants in the present study matched a series of milk samples to musical notes. They chose both the pitch and the class of instrument that they felt was most appropriate for each sample. Participants also rated various features of the samples, such as their pleasantness, bitterness, or familiarity. Consistent associations between flavours and both pitch and instruments were confirmed. However, fat content did not influence either the pitch or instrument chosen, although it did have an effect on pleasantness and intensity ratings. These results demonstrate that flavour-sound associations are not restricted to basic tastes and flavours presented individually, but are still present in the context of more complex food stimuli. The present study opens the way for further investigations into the nature and characteristics of crossmodal associations (or correspondences) between more complex stimuli, both in the auditory and gustatory/olfactory modalities. This novel approach could lead to new insights into the representation of chemosensory stimuli in humans.